The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.brainres.2015.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Resisting false recognition: An ERP study of lure discrimination

Abstract: There is keen interest in what enables rememberers to differentiate true from false memories and which strategies are likely to be the most effective. This study measured electrical brain activity while healthy young adults performed a mnemonic discrimination task, deciding whether color pictures had been studied, were similar to studied pictures (lures), or were new. Between 500 and 800 ms post-stimulus, event-related potentials (ERPs) for correctly recognized studied pictures and falsely recognized lures com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 81 publications
5
24
0
Order By: Relevance
“…This may also be why responses here but not in the previous study were also less accurate for lures than for studied and novel items. The pattern observed here is consistent with previous findings of reduced performance for lures (e.g., Stark et al, 2013;Toner et al, 2009), and with claims that lure discrimination places greater demands on pattern separation (Kirwan and Stark, 2007; and/or post-retrieval processing (Brainerd et al, 2003;Morcom, 2015) and is therefore associated with reduced accuracy.…”
Section: Behavioural Findingssupporting
confidence: 92%
“…This may also be why responses here but not in the previous study were also less accurate for lures than for studied and novel items. The pattern observed here is consistent with previous findings of reduced performance for lures (e.g., Stark et al, 2013;Toner et al, 2009), and with claims that lure discrimination places greater demands on pattern separation (Kirwan and Stark, 2007; and/or post-retrieval processing (Brainerd et al, 2003;Morcom, 2015) and is therefore associated with reduced accuracy.…”
Section: Behavioural Findingssupporting
confidence: 92%
“…Some studies observed the LPP only for true memories (e.g., Curran, 2000;Poch et al,2019), suggesting that lure false alarms are driven by familiarity. However, others have demonstrated that the LPP is observable during lure discrimination independent of memory success (e.g., Curran & Cleary, 2003;Morcom, 2015), suggesting that lure discrimination requires the recovery of mnemonic detail and evokes recollection. While we cannot clearly dissociate the relative contribution of familiarity and recollection in the present paradigm, the onset of the present effect falls within a similar time range (500-800 ms) as the well-established ERP marker of recollection and demonstrates a maximum over posterior channels, supporting our interpretation of alpha/beta desynchronization during retrieval as an index of the specificity of the retrieved content.…”
Section: Alpha/beta Desynchronization Supports Item Recognition and Lmentioning
confidence: 99%
“…According to dual-process models of recognition memory, recognition performance is the result of the collaboration of two different types of processes: recollection and familiarity [ 26 – 28 ]. The Recollection process is thought to be similar to that used in free recall, as it implies the retrieval of contextual details from the moment a certain event was previously encoded [ 27 , 29 ]. In this process, memory judgements are made based on the retrieval of qualitative information, therefore involving the conscious recollection of the prior occurrence of a certain event [ 22 , 30 ].…”
Section: Introductionmentioning
confidence: 99%